P14.96 Gliomatosis cerebri imaging pattern: a treatment-independent marker for worse overall survival in WHO grade II and III gliomas. (6th September 2019) - Divé, I; Steidl, E; Wagner, M; Burger, M C; Franz, K; Harter, P N; Bähr, O; Fokas, E; Herrlinger, U; Steinbach, J P
Abstract: BACKGROUND: The term gliomatosis cerebri (GC) refers to glial brain tumors with widespread tumor expansion affecting three or more cerebral lobes. Formerly considered a distinct tumor entity, recent studies found no difference in the mutational profile of glial tumors with GC growth pattern compared to non-GC gliomas. Thus, in the new WHO classification of brain tumors, GC is no longer included as a separate diagnosis. While the presence of gliomas with GC growth pattern is associated with worse overall survival (OS), the underlying factors remain to be identified. Here, we asked whether differing therapeutic strategies in first line treatment could account for the worse outcome of patients with GC growth pattern and grade II and III histology. MATERIAL AND METHODS: From the patient data bank of the University Cancer Center (UCT) Frankfurt, 47 patients with histological diagnosis of WHO grade II or III glioma, and with record of GC imaging pattern were identified. GC tumor expansion was confirmed by review of MRI scans prior to treatment initiation. Patients with WHO grade II or III glioma without GC growth pattern served as control cohort (n=379). IDH mutational status was available for 75% of GC tumors (IDH R132H mutated 32%; non-mutated 43%) and 69% of non-GC tumors (IDH R132H mutated 57%; non-mutated 12%). RESULTS: Within the GC patient cohort, patients with tumors without contrast enhancement, lower WHO grade and mutated IDH status showed better OS. Compared to the control cohort, patients with GC had significantly shorter OS. This was independent of histological diagnosis or IDH mutation status. Patients with GC more frequently underwent radiochemotherapy (17% vs. 9% in the non-GC cohort), and drastically more often received chemotherapy alone (51% vs. 5%). We then analyzed OS in GC and non-GC patients that had received the same first line treatments. For radiochemotherapy in GC versus non-GC patients, OS was 1.1 years vs. 12.7 years (p =0.0075, log-rank test). For upfront chemotherapy alone, OS was significantly shorter in the GC cohort than in the non-GC cohort (3, 6 years vs. undefined, p =0.0016, log-rank test). CONCLUSION: Differences in first-line treatment cannot account for the worse prognosis of patients with GC imaging pattern. Further studies are needed to pinpoint biological or clinical factors that might influence responsiveness to therapy and prognosis of GC tumors.